1989
DOI: 10.1177/019459988910100111
|View full text |Cite
|
Sign up to set email alerts
|

Primary Placement of Osseointegrated Implants in Microvascular Mandibular Reconstruction

Abstract: The goal of mandibular reconstruction is to rehabilitate the patient by restoring occlusal relationships, lower facial contour, oral continence, and a denture-bearing surface. One of the major advantages of the use of vascularized bone over all other methods of mandibular reconstruction is its ability to achieve dental rehabilitation rapidly. The use of osseointegrated dental implants is a valuable adjunct in oral rehabilitation. It provides the most rigid form of stabilization to withstand the forces of masti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(84 citation statements)
references
References 20 publications
(7 reference statements)
0
80
0
4
Order By: Relevance
“…The use of osseointegrated implants for dental rehabilitation has previously been much more extensively discussed in the context of mandibular reconstruction than that of maxillary reconstruction. [95] Some fundamental concepts of functional dental restoration with prosthetics should be understood. The reconstruction should provide for retention, support, and stabilization of the denture.…”
Section: Osseointegration Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of osseointegrated implants for dental rehabilitation has previously been much more extensively discussed in the context of mandibular reconstruction than that of maxillary reconstruction. [95] Some fundamental concepts of functional dental restoration with prosthetics should be understood. The reconstruction should provide for retention, support, and stabilization of the denture.…”
Section: Osseointegration Techniquesmentioning
confidence: 99%
“…[96] Three to 8 months after placement, the osseointegrated implants are uncovered and prepared for final prosthetic reconstruction by a prosthodontist. [95] The use of free tissue transfer techniques in combination with osseointegrated implants for maxillary reconstruction has been reported by various authors. [97] Holle et al [98] described a two-stage procedure for the reconstruction of maxillectomy defects.…”
Section: Osseointegration Techniquesmentioning
confidence: 99%
“…The fibula also has a low profile relative to the height of the native mandible in dentulous patients. In patients in whom osseointegrated implants are planned as either a primary or a secondary procedure, the fibula should be placed about 0.5 to 1 cm above the inferior border of the native mandible, closer to the superior alveolar edge, to facilitate the placement of implants; alternatively, a double-barrel fibula can be used (Chang et al, 1998;Urken ML et al, 1989 ;Sclaroff A, 1994). However, this requires an adequate skin paddle because more soft tissue is often needed to accommodate the extra bony volume.…”
Section: Reconstruction Of the Mandiblementioning
confidence: 99%
“…16 The placement of implants before and after radiotherapy has been reported and a period of 6 weeks between reconstruction and radiation therapy was recommended. 17 On the other hand, it was also reported that postoperative radiation increases the risk of loosening of implants and osteoradionecrosis. 18,19 Placement of implants after radiotherapy prevents loosening of implants.…”
mentioning
confidence: 99%